Yabancılık unsuru taşıyan iş sözleşmelerine uygulanacak hukuk - Yumuşakbaş, Gamze Nur Zencir (My University, 2019)
İş sözleşmesi, işçinin bağımlı olarak iş görmeyi, işverenin de ücret ödemeyi üstlenmesinden oluşan sözleşmedir. İş sözleşmesinin tarafları olan işçi ve işveren eşit durumda olmadığı için, iç hukukta olduğu gibi milletlerarası özel hukukta da sözleşmenin zayıf tarafı olan işçinin korunması asıldır. Çalışmamızın amacı, yabancılık unsuru taşıyan iş sözleşmelerine uygulanacak hukukun tespitini yapmaktır. Bu tespit yapılırken öncelikle maddi hukukta iş sözleşmesi incelenmiştir. Takiben iş sözleşmesine uygulanacak hukukun tespiti yapılmış; ROMA I Tüzüğü ile karşılaştırmalı olarak 5718 sayılı Milletlerarası Özel Hukuk ve Usul Hukuku Hakkında Kanun'un 27. maddesi incelenmiştir. An employment contract is a contract which a worker undertakes to work as a dependent and an employer undertakes to pay wages. As the employer and the employee that are the interested parties of the employment contract are not equal, the protection of the employee who is the weak side of the contract is essential in international private law as well as in domestic law. The aim of our study is to determine the applicable law in the contract of employment containing foreign element. While making this determination, firstly, the employment contract in the substantive law was examined. Then, the law to be applied to the employment contract was determined; Article 27 of the Law No. 5718 on International Private and Procedural Law has been examined in comparison with the ROME I Regulation.
Keywords: İş sözleşmesi; milletlerarası özel hukuk; uygulanacak hukuk; uygulanacak hukuk İş sözleşmesi